Third Harmonic Injection Reference with Edge Shifted Carriers to Three Phase Inverter Fed Induction Motor - Bhavana Kadiyala; R. Bensraj; P. Muthukumar (Statistics, Optimization & Information Computing, 2025)
A three-phase induction motor (IM) fed by an inverter is widely used in industrial and commercial drives because it can effectively convert Direct Current (DC) power to balanced three-phase Alternative Current (AC) power, which is suitable for driving IMs. Pulse Width Modulation (PWM) switching introduces harmonics into the output voltage, which can cause additional heating of the motor, torque ripple, and electromagnetic interference (EMI). This research investigates the design and performance improvement of a three-phase Voltage Source Inverter (VSI) system for effective IM operation, combined with a new Kookaburra-based Modular Neural Control Framework (KbMNCF). The first step is designing a conventional VSI topology using a DC voltage source, power electronic switches, and PWM to convert the DC input into a balanced three-phase AC output for industrial motor drives. To maximize inverter performance while adapting the control, the introduced KbMNCF is used to tune the PWM parameters. The PWM techniques adopted include Third Harmonic Injection (THI) for maximizing output voltage and an Edge-Shifted Carrier (ESC) method to allocate switching actions, thereby minimizing switching losses and thermal stress. The system's overall robustness is confirmed by assessing key performance metrics, including Total Harmonic Distortion (THD), Voltage, and system efficiency. Simulation and analysis have demonstrated significant improvements in waveform quality, torque smoothness, and energy efficiency, thereby verifying the validity of the proposed control framework for high-performance inverter-fed motor drives.